Diagnosis of ecosystem misconceptions for high school students in Jakarta - Azrai, Eka Putri; Japar, Muhammad; Situmorang, Robinson (International Journal of Evaluation and Research in Education (IJERE), 2025)
Misconception is a condition of different concepts that are owned by scientific concepts. Misconceptions impact learning processes and outcomes, so teachers need to make reductions. The first step to reduce misconceptions is to find the data on students’ misconceptions. This study aims to diagnose high school students’ misconceptions about ecosystems. The survey method research used a three-level multiple-choice test to diagnose ecosystem misconceptions. The research sample were 200 high school students from five high schools in Jakarta, Indonesia. The sample from each school were 40 students. The results showed that students’ understanding of concepts was spread over six levels: understanding concepts, false positive misconceptions, false negative misconceptions, misconceptions, guessing or understanding concepts but lacking confidence, and not understanding concepts with a misconception percentage of 21.41%. Based on the analysis of the ecosystem sub-concept, the highest misconception occurred in the energy flow sub-concept (25.39%) and the second highest in the biogeochemical cycle sub-concept (20.41%). Teachers can use the findings as a basis for designing effective learning to reduce misconceptions so that optimal learning processes and results can be achieved.